2020
DOI: 10.1002/fsn3.1396
|View full text |Cite
|
Sign up to set email alerts
|

Optimized extraction and quality evaluation of Niger seed oil via microwave‐pulsed electric field pretreatments

Abstract: In this study, oil extraction from Niger seeds was evaluated with different microwave irradiation times (0–200 s) and pulsed electric fields (PEF) intensities (0–5 kV/cm) as pretreatments. Then, oil extraction was completed with a screw press at different rotation speeds (11–57 rpm). Quality parameters including extraction efficiency, acidity and peroxide values (PVs), chlorophyll, and phenolic contents along with fatty acid profiles and tocopherol levels of the extracted oils were determined as responses. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…An explanation for this phenomenon could be the use of this pretreatment that leads to tissue degradation and creating more pores and outputs, resulting in better extraction of oil from the seeds. Reducing the extraction efficiency of oil by excessively increasing the intensity of the electric field can also be attributed to further degradation of the inner structure of the seeds and the closure of the oil output ducts (Mohseni et al, 2020a, 2020b).…”
Section: Resultsmentioning
confidence: 99%
“…An explanation for this phenomenon could be the use of this pretreatment that leads to tissue degradation and creating more pores and outputs, resulting in better extraction of oil from the seeds. Reducing the extraction efficiency of oil by excessively increasing the intensity of the electric field can also be attributed to further degradation of the inner structure of the seeds and the closure of the oil output ducts (Mohseni et al, 2020a, 2020b).…”
Section: Resultsmentioning
confidence: 99%
“…Also, carbohydrate is a major energy source for plants [ 64 ]. Carbohydrate synthesis correlates with plants' chlorophyll, water, and carbonic gas function [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, combing the pretreatments techniques was reported to affect the oil fatty acid composition significantly. In their study on microwave-pulsed electric field pretreatment (microwave time: 0-200 s, pulse intensity: 0-5 kV/cm) of niger seeds, Mohseni et al (2020a) reported that the quantity of oleic and linoleic acids significantly decreased.…”
Section: Fatty Acidsmentioning
confidence: 99%
“…Integrating pretreatment techniques is a novel and promising technology to optimise the extraction of valuable compounds from plant materials. For example, Mohseni et al (2020a) established that integrating microwave (900 W, 0-200 s) and pulsed electric field (0-5 kV/ cm, 20 ls) and pretreating niger seeds increased the oil atocopherol and D-tocopherol by 2.8%. Similar observations were reported by Mohseni et al (2020b) with rapeseeds (Table 3).…”
Section: Effect Of Novel Seeds Pretreatment Techniques On Oil Bioactive Compounds Tocopherolsmentioning
confidence: 99%